2020
DOI: 10.1007/s43069-020-00028-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Market Stochastic Dynamics

Abstract: A Feynman-type path integral has been introduced to find an optimal strategy where a dynamic profit is maximized subject to a stochastic dynamics of a firm's market share. This method is useful under a more generalized non-linear system such as the Merton-Garman-Hamiltonian process where constructing a Hamiltonian-Jacobi-Bellman equation is very difficult. The path integral method also gives an optimal strategy without going through a value function and gives a different optimal strategy. The result obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…And also, the risk aversion of a bank affects the interest income and the negative correlation between credit risk and interest rate. Pramanik [30] and Pramanik, & Polansky [31] developed an optimization technique to indemnify the macroeconomic variables that impact the interest rate spread.…”
Section: B Empirical Findingsmentioning
confidence: 99%
“…And also, the risk aversion of a bank affects the interest income and the negative correlation between credit risk and interest rate. Pramanik [30] and Pramanik, & Polansky [31] developed an optimization technique to indemnify the macroeconomic variables that impact the interest rate spread.…”
Section: B Empirical Findingsmentioning
confidence: 99%
“…Firms always search for the optimization of profits with highest efficiency. [22]. When the foreign exchange rate is favorable, foreign direct investment increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Khathlan [10] examined the determinants of inflation in Kingdom of Saudi Arabia for the period 1980 to 2009 and found that in the long run the global inflation rate and exchange rate have substantial influence whereas in the short run, money supply and supply bottlenecks are the major determinants of inflation. Pramanik & Polansky, [11] found an efficient optimization technique to control the macroeconomic variables to reach an optimum solution. Similarly, Pramanik [12] and & Pramanik & Polansky [13] reached the same conclusion using the dynamic profit function.…”
Section: Literature Reviewmentioning
confidence: 99%